Binocular portraiture. (March 2023) - Wade, Nicholas J.
Pictorial portraits are viewed with two eyes despite the fact that they are mostly monocular: they have been produced from a single viewpoint (either by painters or photographers). The differences between the images on each eye are a consequence of the separation between them rather than differences in two pictorial images. Viewing with two eyes detracts from the monocular cues to depth within the singular portrait because of information for the flatness of the pictorial surface. Binocular portraits, on the other hand, incorporate differences between two pictorial images producing perceptual effects that cannot be seen by a single eye alone. The differences can consist of small disparities that yield stereoscopic depth or large ones that produce binocular rivalry. Binocular portraits require viewing with a stereoscope, many varieties of which exist. Those shown here are anaglyphs which can be observed through red/cyan filters. They are not conventional stereoscopic portraits where the sitter is imaged from two slightly different locations. Rather, the binocular processes of cooperation (stereoscopic depth perception) and competition (binocular rivalry) are manipulated in the binocular portraits. The subjects shown in the anaglyphic portraits have been involved in the science and art of binocular vision.